СПОСТЕРІГАЧ ПОТОКОЗЧЕПЛЕННЯ, АДАПТИВНИЙ ДО ЗМІН АКТИВНОГО ОПОРУ РОТОРА АСИНХРОННИХ ДВИГУНІВ - Пересада, С.М.; Ніконенко, Є.О.; Ковбаса, С.М.; Кузнецов, О. (Інститут електродинаміки НАН України, Київ, 2022)
A flux observer for induction motors which is adaptive to the active rotor resistance variations is presented. Due to the added fluxes overestimation in the observer structure, the global exponential stability properties of the current and flux vector components and active rotor resistance estimation are ensured under conditions of persistency of excitation. The proposed observer has a simpler structure compared to existing solutions with the global stability properties. The simulation results of the observer dynamic performance investigation confirm its effectiveness. It is shown that even if the conditions of persistency of excitation are not met, the active rotor resistance is estimated correctly; consequently, the designed observer can be implemented as an identification algorithm in self-commissioning systems of induction electric drives. References 9, figures 5.